(untitled) (Biocenosis, 2021)
We investigate the Environmental Education process carried out by three Administrative Associations of Water Supply and Sewerage Systems (ASADAS, for its acronym in Spanish). We describe the EE activities carried out by these entities, which, in addition to supplying drinking water, must protect the hydric resource. The purpose of this publication is to inform about the role that ASADAS are playing both in hydric resource protection and in biodiversity conservation. This information is useful to improve what the studied ASADAS have done so far, and to promote environmental education in other associations. The study required documentary review, semi-structured interviews, and questionnaire application to key informants. Among the most relevant environmental education activities developed by the ASADAS are spring georeferencing, reforestation, training, special date celebrations, project formulation, solid waste management, protected areas damage reports, and field trips.